Heroism – national spiritual value (Journal of Philosophy Culture and Political Science, 2018)
This article touches on the notion that emerged from the times of ancient Kazakhs and entrenched in the minds of our ethnic group, the concept has become one of the symbols of national spiritual values, touches on the notion of heroism (courage). Step is performed in order to study the dynamics of heroism in the direction of the epic, the disclosure of its internal scientific and logical sense. Determined by the social role of the concept of «heroism», his status in society, ideological sense, the status of spiritual and cultural values and taken efforts to disclose the educational role of the concept. Key words: heroism, national, spiritual, values, filogemy, tempotsentrizm, personality, human world (personal world).